What Does ‘Information’ Mean in Integrated Information Theory? - Olimpia Lombardi; Cristian López (Entropy, 2018)
Integrated Information Theory (IIT) intends to provide a principled theoretical approach able to characterize consciousness both quantitatively and qualitatively. By starting off identifying the fundamental properties of experience itself, IIT develops a formal framework that relates those properties to the physical substratum of consciousness. One of the central features of ITT is the role that information plays in the theory. On the one hand, one of the self-evident truths about consciousness is that it is informative. On the other hand, mechanisms and systems of mechanics can contribute to consciousness only if they specify systems’ intrinsic information. In this paper, we will conceptually analyze the notion of information underlying ITT. Following previous work on the matter, we will particularly argue that information within ITT should be understood in the light of a causal-manipulabilist view of information (López and Lombardi 2018), conforming to which information is an entity that must be involved in causal links in order to be precisely defined. Those causal links are brought to light by means of interventionist procedures following Woodward’s and Pearl’s version of the manipulability theories of causation.